Reduction of pollution by controlled disposal of hazardous pharmaceuticals. Issue 1 (February 2021) - Ardelean, E; Ordodi, V; Ardelean, M; Socalici, A; Lemle, K L
Abstract: Human activities generate a series of waste increasingly more complex and difficult to manage (through the containment, inertization or destruction). Particular attention must be paid to hazardous waste with a high risk of environmental pollution but especially for infestation to the human generator. In this context, we considered the possibility of integrated waste management resulted from the pharmaceutical industry, which is frequently mishandled and ends (reach) in the environment. This paper proposes a method for neutralizing some hazardous pharmaceutical waste, using electrochemical methods for inactivation, respectively an electrochemical reactor with asymmetric current densities. The results obtained in the laboratory for four of these substances leads to the generation of viable solutions that can be used in practice.